Digital Teaching Transformation: Challenges, Strategies, and Future Prospects in Macroeconomics Education - Hu, Zhilin (International Journal of Education and Humanities, 2024)
With the rapid development of educational technology, the teaching methods in macroeconomics are undergoing a profound digital transformation. This paper comprehensively explores the methods, assessment of effectiveness, challenges faced, and the construction content and strategies of digital teaching in macroeconomics, aiming to provide insights and guidance for educators to implement digital teaching effectively. By analyzing the application of teaching tools such as online classrooms, interactive simulation software, and data analysis tools, this study reveals the potential of these methods in enhancing student motivation and understanding of macroeconomic theories. However, challenges such as technological issues, adaptability in teaching, and resource allocation still need to be overcome through continuous technological innovation and policy support. The article concludes with suggestions for future research and policy-making, emphasizing the importance of the concurrent development of educational technology and teaching practices